Nonredundant Hexagonal Grid Interferometer Configurations with Element-Free Central Domains - Kopilovich, L.E. (Радиофизика и радиоастрономия, 2004)
Nonredundant hexagonal grid interferometers having element-free central domains are configured with the difference set procedure. The obtained configurations possess third-order symmetry that provides more uniform coverage of the spatial-frequency plane.